Characterization and structural analysis of RF magnetron sputtered strontium stannate thin films - Yusmar Palapa Wijaya; Khairul Anuar Mohamad; Abu Bakar Abdul Rahman; Afishah Alias; Mohammad Syahmi Nordin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This paper presents physical and morphology properties of strontium stannate (SrSnO3) perovskite-type as a candidate of an n-type material thin film for organic-inorganic hybrid diode heterojunction for optoelectronics application. Typical wet-process of SrSnO3 deposition produce thick film and having 10-8 S/cm order in conductivity. The SrSnO3 thin films were deposited on ITO glass substrates by RF magnetron sputtering using a purity 99.9% SrSnO3 target with 5.0 mTorr of gas pressure and 100 W of RF power at room temperature. The gas composition of pure argon (75%) and reactive oxygen gas (25%) was used for 60 min. XRD diffraction patterns revealed that the thin films are orthorhombic crystal structure with lattice parameter a=5.7040 Ǻ, b=8.06 Ǻ and c=5.7080 Ǻ with a strong orientation in the (002) direction. SEM images showed that films exhibited uniform surface morphology with a roughness average of Ra=2.258 nm and thickness of 311 nm. The EDX spectrum confirmed the presence of O, Sr, and Sn elements in the films with 75.22%, 8.29%, 16.49% in atomic number, respectively. The films were having a conductivity of 8.33x102 S/cm with low resistivity of 12.4x10-3 W-cm.